Polyphenol metabolomics reveals the applications and prospects of polyphenol-rich plants in natural dyes - Jing Gao; Yunxiao Zhao; Feifei Ni; Ming Gao; Liwen Wu; Zhicheng Yu; Yicun Chen; Yangdong Wang (Forestry Research)
Polyphenols, as one of the primary compounds produced by plant secondary metabolism, have garnered considerable attention because of their non-toxic, environmentally friendly, and biodegradable properties, as well as their notable medicinal value. This study presents a metabolomic analysis of polyphenols from 11 woody plants, including Camellia oleifera, Quercus acutissima, and Punica granatum, investigating a total of 40 polyphenolic metabolites. A differential metabolite dynamics map highlighted the five most differentiated substances among the 11 plants, including vitexin, dihydromyricetin, genistin, resveratrol, and isorhamnetin. To evaluate the application of polyphenol-rich plants as natural dyes, dye performance tests, and color fastness evaluations were conducted, focusing on the specific role of polyphenols in dyeing cotton fabrics. The composition of polyphenols had a minor effect on the color of dyed cotton fabrics, typically imparting only black or brown tones to the fabric. However, their effect on dyeing performance is notable, with the ratio of the dye absorption coefficient (k) to the dye scattering coefficient (s) (K/S) ranging from 1 to 20, and lightness varying from 26 to 78. The addition of mordants not only improved the dye's color fastness but also expanded the color range. Furthermore, this study identified four key substances that influence the dyeing performance of plant dyes, including naringenin, epicatechin, catechin, and dihydromyricetin, and discovered a novel natural dye compound, naringenin. Importantly, six of the 11 plant dyes selected in this study are derived from plant waste, thus providing a theoretical basis for advancing environmentally friendly and sustainable dyeing technologies.